Our Fair Seattle Belle - Delahunty, Adelina B.
1907 The music and lyrics for "Our Fair Seattle Belle" were written by Adelina B. Delahunty, a Seattle school teacher. The song was written for the Alaska-Yukon-Pacific Exposition (AYPE), a world's fair held in 1909 on the campus of Seattle's University of Washington to promote the development of the Pacific Northwest. 1 score (6 p.) + 1 part 10.5 x 14 in.